Toxicity of water-soluble polymers polyethylene glycol and polyvinyl alcohol for fish and frog embryos - Zicarelli, Giorgia; Faggio, Caterina; Blahova, Jana; Riesova, Barbora; Hesova, Renata; Doubkova, Veronika; Svobodova, Zdenka; Lakdawala, Pavla (The Science of the total environment, 2024)
Personal Care Products (PCPs) have been one of the most studied chemicals in the last twenty years since they were identified as pseudo-persistent pollutants by the European Union in the early 2000s. The accumulation of PCPs in the aquatic environment and their effects on non-target species make it necessary to find new, less harmful, substances. Polyethylene glycol (PEGs) and polyvinyl alcohol (PVAs) are two polymers that have increased their presence in the composition of PCPs in recent years, but little is known about the effect of their accumulation in the environment on non-target species. Through embryotoxicity tests on two common models of aquatic organisms (Danio rerio and Xenopus laevis), this work aims to increase the knowledge of PEGs and PVAs' effects on non-target species. Animals were exposed to the pollutant for 96 h. The main embryotoxicity endpoint (mortality, hatching, malformations, heartbeat rate) was recorded every 24 h. The most significant results were hatching delay in Danio rerio exposed to both chemicals, in malformations (oedema, body malformations, changes in pigmentation and deformations of spine and tail) in D. rerio and X. laevis and significant change in the heartbeat rate (decrease or increase in the rate) in both animals for all chemicals tested.
Keywords: embryo nesavčí; Xenopus laevis; dánio pruhované; Surface waters; Water Pollutants, Chemical; Emerging contaminants; Polyvinyl Alcohol; Toxicity Tests; Animals; zvířata; Aquatic toxicity; polyvinylalkohol; Zebrafish; polyethylenglykoly; Danio rerio; chemické látky znečišťující vodu; Embryo, Nonmammalian; testy toxicity; Polyethylene Glycols